UWAGI NA TEMAT PROCEDURY ‘OBNUNTIATIO’ - Loska, Elżbieta (Zeszyty Prawnicze, 2016)
SOME REMARKS ON THE ‘OBNUNTIATIO’ PROCEDURE Summary The relation between law and religion that existed in Rome before the foundation of the City appeared especially strong towards the end of the Republic. It seems that the reason behind was the possibility of using the religious measures to achieve a political effect. One of the measures was obnuntiatio – a possibility to announce prohibitive signs, connected with auspicia. There were certain leges, through which the use of obnuntiatio was controlled – lex Aelia, lex Fufia and lex Clodia. There is now only a limited possibility to settle the exact content of the leges and their relations to one another. But undoubtedly this procedure was a dangerous political tool when misused in a conscious way.